2013
DOI: 10.1136/vr.101063
|View full text |Cite
|
Sign up to set email alerts
|

A prospective on farm cohort study investigating the epidemiology and pathophysiology of drunken lamb syndrome

Abstract: Drunken lamb syndrome (DLS) is a fatal disease of unknown aetiology affecting young lambs. In 2011, a prospective on farm cohort study was carried out to investigate the epidemiology and pathophysiology of DLS. Ten cases from a cohort of 1635 crossbred and pure Welsh Mountain lambs were identified as having DLS on the basis of characteristic clinical signs. Renal histopathology demonstrated nephrosis in all 10 cases. Some cases also demonstrated concurrent intestinal pathology. The cases were significantly sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 12 publications
(15 reference statements)
1
13
0
Order By: Relevance
“…8 Similar findings of D-lactic acidosis have been reported in young ruminants as well as cats with gastrointestinal disease. [11][12][13][14][15] Increased D-lactate concentrations could be present in CPV dogs considering the destruction of the protective intestinal epithelium, resultant maldigestion, risk of bacterial translocation, and the ability for systemic absorption of increased D-lactate via MCT1 transporters in the colon.…”
Section: Introductionmentioning
confidence: 99%
“…8 Similar findings of D-lactic acidosis have been reported in young ruminants as well as cats with gastrointestinal disease. [11][12][13][14][15] Increased D-lactate concentrations could be present in CPV dogs considering the destruction of the protective intestinal epithelium, resultant maldigestion, risk of bacterial translocation, and the ability for systemic absorption of increased D-lactate via MCT1 transporters in the colon.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we introduced a novel case definition of LDLAS based on developments in our understanding of DLS (Angell and others 2013). Of the 23 lambs presented by the farmers with clinical signs suggestive of DLS, five lambs did not fit the revised case definition since they had no evidence of metabolic acidosis and were thus excluded.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous paper (Angell and others 2013), we described the clinical, epidemiological, histopathological and biochemical picture of 10 lambs with drunken lamb syndrome (DLS). All 10 cases in that study presented with marked ataxia tending to recumbency.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work by Angell and others (2013) suggested that nephrosis is a consequence of D-lactate acidosis, possibly of intestinal microbial origin.…”
Section: Small Ruminantsmentioning
confidence: 99%